ژیانی کۆمەڵایەتی گەڕەکی سابونکەران توێژینەوەیەکی ئەنسرۆپۆلۆجی - هەرزانی, پ.ی.د.نوری یاسین; سعید, بژوێن عمر محمد (Sulaimani Journal for Humanities, 2023)
This research works scientifically to explain how the social life of the Sabunkaran neighbourhood is based on the stages of history it has gone through. The content of the study focuses on scientific research on the characteristics and differences of marriage, family, and kinship of the Sabunkaran neighborhood in anthropology, the Sabunkaran neighborhood is the residence of intellectuals, educated people and poets... Etc., the level of enlightenment of its population has affected the quality of its social life.